1989
DOI: 10.1007/bf02636188
|View full text |Cite
|
Sign up to set email alerts
|

Soy oil lutein adsorption by rice hull ash

Abstract: Rice hull material was converted to an adsorbent of the soy oil pigment, lutein, by a combination of ashing and acid activation. Pigment was adsorbed from a 20% (v/v) soy oil/hexane miscella. The most effective ashing temperature was 500°C. Five percent acid activation significantly promoted adsorption of the ash, but greater acid activation did not increase adsorption capacity very much. In the system studied, the performance of activated ash was comparable to that of activated bleaching earth. Nonactivated a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
23
0

Year Published

1992
1992
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(26 citation statements)
references
References 6 publications
3
23
0
Order By: Relevance
“…Thus, 500°C was the optimal temperature for the production of rice hull ash. Present findings confirm those of Proctor and Palaniappan (3).…”
Section: By Dotted Linessupporting
confidence: 95%
See 2 more Smart Citations
“…Thus, 500°C was the optimal temperature for the production of rice hull ash. Present findings confirm those of Proctor and Palaniappan (3).…”
Section: By Dotted Linessupporting
confidence: 95%
“…Increasing the ashing temperature decreases the bleaching ability of the ash (3,4). Proctor and Palaniappan (3) found that the most effective ashing temperature in the range of 500-1,000°C was 500°C, but Liew et al (4) observed that heat treatment of rice hull at temperatures below 300°C resulted in the most active adsorbent after acid activation.…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…Proctor and Palaniappan [31] found that a silicate material derived from rice husk ash was capable of binding lutein from soy oil in hexane at room temperature. Acid washing lowered the ash pH and enhanced lutein adsorption by the ash.…”
Section: Absorbentmentioning
confidence: 99%
“…These same observations were made by Salawudeen et al (2007) while evaluating the effectiveness of acid treated clays for palm oil bleaching. Proctor and Palaniappan (1989) and Brace (1973) attributed the high adsorptive power of HCl activated clays to the complete removal of aluminium, magnesium and calcium ions within the crystal of the clay. Based on these explanations, it may be inferred that impurities such as Fe 2 O 3 , CaO and MgO e.t.c that cover part of the active sites are washed away by acid activation and the number of active site available for adsorption increased (Salawudeen et al, 2007).…”
Section: Performance Of Adsorbents Samples In the Bleaching Of Palm Oilmentioning
confidence: 99%